The relevance of the current Zimbabwean ordinary level mathematics curriculum to industry: a case of Gweru Urban - Mashingaidze, Samuel; Bandera, Caroline (International Research Journals, 2016)
Research works on mathematics curriculum relevance abound. These efforts are to help substitute no longer relevant curricula with vibrant ones that can boost national development. This study investigated the relevance of the current Ordinary Level Mathematics curriculum (4008/4028) to vocational training and the workplace (Industry) in Gweru urban area. A descriptive survey approach was used to collect the relevant data. Anonymous questionnaires were completed by eighty college students (forty-two females and thirty-eight males) and ten college lecturers (six males and four females). Interviews were conducted with twenty high school Mathematics teachers (twelve females and eight males) and ten people from the workplace (six males and four females). The study gave empirical evidence that although the curriculum is relevant on paper challenges encountered fall on its implementation, as students in vocational training are unable to recognize, apply and link high school Mathematics to Mathematics in vocational training and the workplace. This is partly explained by teacher strategies that have little or no real life implications. Although school mathematics teachers indicated that they were aware of what vocational needs are, they raised concerns about several factors that impact on them being effective in lesson delivery. The study recommends that the Ministry of Education, Sport, Arts and Culture should provide mandatory in-service training for Mathematics teachers so that they keep abreast of the developments in Mathematics education issues. High school Mathematics teachers should link Mathematics in school to vocational training and the workplace by occasionally taking pupils to places where Mathematics is applied.